The fundamental understanding of the impact using brain-breaks on Sarawakian indigenous children based on physical activity, nutrition and hygiene: a united nation sdg project - #3 good health and well being - Len, Lim Ting (2023)
This study aimed to investigate the effects of using brain-breaks on physical activity behaviour, health-related fitness, food intake, and personal hygiene among the indigenous primary school children in Sarawak, Malaysia. The participants were 70 indigenous primary school children (38 male and 32 female) aged 10 to 12 years old from two rural schools in Sarawak, Malaysia. The health-related fitness test was conducted to evaluate the students’ flexibility, muscular strength, muscular endurance, body composition and cardiovascular endurance. The nutritional status of an individual was calculated using three days’ food record, involving two-week days and one weekend. The hygiene of an individual was recorded using personal hygiene record. Descriptive statistics and mixed factorial ANOVA were used to analyse the data. The mixed factorial ANOVA for health-related fitness revealed significant changes for group effect on vertical jump, F(1, 68) = 7.26, p-value (ηp2) = .009 (.096), push up, F(1, 68) = 89.06, p-value (ηp2) < .001 (.567) and beep test, F(1, 68) = 4.53, p-value (ηp2) = .037 (.062). Whereas, the mixed factorial ANOVA for food intake revealed significant changes for group effect on weekday 2 calories intake, F(1, 68) = 19.94, p-value (ηp2) < .001 (.227) and weekday 3 calories intake, F(1, 68) = 89.93, p-value (ηp2) < .001 (.569). Lastly, the mixed factorial ANOVA for personal hygiene revealed significant changes for group effect on brush hair, F(1, 68) = 4.43, p-value (ηp2) = .039 (.061), make bed, F(1, 68) = 21.00, p-value (ηp2) < .001 (.236), put on pajamas, F(1, 68) = 12.91, p-value (ηp2) = .001 (.160), and cut nails, F(1, 68) = 78.34, p-value (ηp2) < .001 (.535). The study recommends school-based brain breaks activity need to be vary, adapt and diversify according to the culture, values and norms in order to improve the health, nutrition and well-being of the indigenous children in the long run.